Volunteer Values ​​in the Implementation of Community Education (Study on the GADABAK! Community in South Solok Regency - Agung Dwi Putra; Encep Syarief Nurdin; Yadi Ruyadi (Universitas Negeri Padang, 2022)
In 2017 Handriva Fauzi founded the GADABAK! in South Solok Regency, West Sumatra Province as a tool to fulfill organizational needs for young people who have an interest in education, arts and culture, tourism and the environment. The research approach used is qualitative with a phenomenological design. The results of this study indicate that the life experience of institutional managers is a manifestation of the impetus that influences the emergence of decisions to take voluntary action as the basis for managing the institution.Keywords: voluntarism, non-formal education, development, community